2011
DOI: 10.1021/bm101110x
|View full text |Cite
|
Sign up to set email alerts
|

Pectin-Based Injectable Biomaterials for Bone Tissue Engineering

Abstract: A variety of natural polymers and proteins are considered to be 3D cell culture structures able to mimic the extracellular matrix (ECM) to promote bone tissue regeneration. Pectin, a natural polysaccharide extracted from the plant cell walls and having a chemical structure similar to alginate, provides interesting properties as artificial ECM. In this work, for the first time, pectin, modified with an RGD-containing oligopeptide or not, is used as an ECM alternative to immobilize cells for bone tissue regenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
131
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(135 citation statements)
references
References 30 publications
4
131
0
Order By: Relevance
“…8,16,17 In tissue engineering and regenerative medicine applications there were just a few studies performed using pectin gels. [18][19][20][21][22] Our group 18,19 has previously explored the external gelation of pectin with CaCl 2 to obtain microspheres for the encapsulation of MC3T3 pre-osteoblast cells, which maintained a constant viability up to 29 days and were able to differentiate. Jahromi et al 22 embedded rat bone marrow stromal cells within citrus pectin hydrogels crosslinked by diffusion with CaCl 2 , within which cells were able to differentiate under osteogenic conditions.…”
mentioning
confidence: 99%
“…8,16,17 In tissue engineering and regenerative medicine applications there were just a few studies performed using pectin gels. [18][19][20][21][22] Our group 18,19 has previously explored the external gelation of pectin with CaCl 2 to obtain microspheres for the encapsulation of MC3T3 pre-osteoblast cells, which maintained a constant viability up to 29 days and were able to differentiate. Jahromi et al 22 embedded rat bone marrow stromal cells within citrus pectin hydrogels crosslinked by diffusion with CaCl 2 , within which cells were able to differentiate under osteogenic conditions.…”
mentioning
confidence: 99%
“…To overcome this limitation, it is considered important to develop pulp regeneration therapy as well as clarify the mechanisms of pulp wound healing. Pulp wound healing and regeneration have common processes, and results of a number of studies have indicated that pulp wound healing consists of initial inductions of apoptosis of damaged pulp cells [134],followed by reactionary dentinogenesis by surviving odontoblasts and reparative dentinogenesis by odontoblast-like cells [150,151]. Reactionary or reparative dentin is formed toward the residual dental pulp, however, not in the area in which the dentin-pulp complex has been lost.…”
Section: Dental Applicationsmentioning
confidence: 99%
“…Many natural polymers including alginate [20] , agarose [21] , atelocollagen [22] , fibrin [23] , collagen [24] , chitosan [25] , and pectin [26] resulting in a gel structure [20,27] . Alginates are among the most frequently employed biomaterials for encapsulation due to their abundance, convenient gelling properties and high biocompatibility [28] .…”
Section: Ehd Compatible Biomaterialsmentioning
confidence: 99%
“…It is a widely available bioactive polymer and FDA approved which may emphasise its translatability. Its use as a single material or in combination with other materials in carrier and capsule systems may allow for an improved injectable formulation [26] .…”
Section: Ehd Compatible Biomaterialsmentioning
confidence: 99%